1934
DOI: 10.1002/j.1551-8833.1934.tb14393.x
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Free Chlorine

Abstract: A number of reagents have been proposed for determination of free chlorine or chloramine in water. Phelps suggested the use of 0tolidine in acetic acid (1) and Ellms and Hauser devised a method for estimation of chlorine based upon the use of o-tolidine in hydrochloric acid (2). The starch iodide test has been used for some time by certain workers. More recent suggestions are the use of dimethylp-phenylenediamine hydrochloride as a reagent for chlorine (3) and methyl orange for the estimation of chlorine in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1937
1937
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…It was concluded that, since the color produced by Cl, or NH2Cl was so unstable, the reagent was not more advantageous than the 30 per cent o-tolidine reagent. This agrees with conclusions from earlier studies made in this laboratory (3).…”
supporting
confidence: 94%
“…It was concluded that, since the color produced by Cl, or NH2Cl was so unstable, the reagent was not more advantageous than the 30 per cent o-tolidine reagent. This agrees with conclusions from earlier studies made in this laboratory (3).…”
supporting
confidence: 94%
“…HOCl is known to form from H2O2 in the presence of Cl ─ and copper ions (70). In the presence of o-tolidine, the ENM0V and ENM3V treated solutions turned yellow due to formation of holoquinone (97), confirming the presence of HOCl in the solution (Fig. 5I and tables S6 ─ S7).…”
Section: Cu(i) Generation By Enm Devicesmentioning
confidence: 64%
“…When the ratio of acid to ortho-tolidine becomes less than 100: 1, the color decreases That low concentrations of ortho-tolidine favor the formation of the holoquinone has been pointed out by Tarvin, Todd and Buswell (12). From the oxidation-reduction standpoint this is plausible.…”
Section: Vol Jsmentioning
confidence: 87%
“…Dragt (15) showed that, as the pH is lowered, the effect of iron interference is lessened. Scott (28,31), Tarvin, Todd and Buswell (12) and others have recommended the use of more ortho-tolidine, ortho-tolidine in additional acid or ortho-tolidine and additional acid to eliminate the interference of iron. This recommendation appears in Standard Methods as a modification of the usual procedure, which specifies the use of 1 m!.…”
Section: Effect Of Acid Concentration or Ph On Ortho-tolidine-chlorinmentioning
confidence: 99%
See 1 more Smart Citation